Surgical site infection in overweight and obese total knee arthroplasty patients - Wilson, C; Georgiou, K; Oburu, E; Theodoulou, A; Deakin, A; Krishnan, J (Elsevier, 2018)
Purpose This aim of this study was to evaluate the rate of surgical site infection (SSI) in patients undergoing Total Knee Arthroplasty (TKA), to improve our understanding of the associations between infection rate and obesity. Methods Data was reviewed for 839 primary TKA procedures performed at a National Arthroplasty Centre over one year (April 2007–March 2008). SSI data was collected at 30 days and one year post-operatively. Patients were grouped guided by the WHO classifications of obesity; normal (BMI < 25.0), overweight (BMI 25.00–29.99), obese class I (BMI 30.00–34.99), obese class II (BMI 35.00–39.99), obese class III (BMI ≥ 40.00). Statistical significance was assessed by Fisher’s Exact Test. Results When grouped by BMI, 30.9% of patients were obese class I, 19.0% obese class II and 8.7% obese class III. Of the total cohort, 22 patients (2.6%) had superficial SSI and 13 (1.5%) had deep SSI. When comparing the obese class III cohort to all other cohorts (non-obese class III), the odds ratios for superficial SSI was 4.20 (95% CI [1.59, 11.09]; p = 0.009) and deep SSI was 6.97 (95% CI [2.22, 21.89]; p = 0.003). In the obese class III cohort, superficial SSI rate was higher in females (8.9%) than males (5.9%), yet deep SSI demonstrated the opposite, with a higher occurrence in males (11.8%) compared to females (5.4%). Conclusion This study suggests that obese class III TKA patients are at increased odds of superficial and deep SSI compared to other BMI cohorts. Interestingly, male obese class III patients demonstrated a higher rate of deep infection compared to their female counterparts. However, it must be noted that study findings are limited as confounders were unable to be accounted for in this retrospective study design.